Seasonality and day-to-day variability of dietary diversity: Longitudinal study of pregnant women enrolled in a randomized controlled efficacy trial in rural Burkina Faso - Hanley-Cook, Giles T.; Argaw, Alemayehu; de Kok, Brenda; Toe, Laeticia Celine; Dailey-Chwalibóg, Trenton; Huybregts, Lieven (Elsevier, 2022)
Background: Panel data indicates that non-pregnant women's dietary diversity fluctuates across climatic seasons in low- and middle income countries. The natural day-to-day variability in food group consumption during gestation is unknown. Objective: A longitudinal study was conducted, among pregnant women enrolled in the MISAME-III randomized controlled efficacy trial [i.e., daily fortified balanced energy-protein supplement and iron-folic acid (IFA) tablet vs IFA tablet only], to investigate the number of 24-h recalls required to estimate usual prenatal food group (FG) diversity and the seasonality of pregnant women's dietary diversity in Houndé, Burkina Faso. Methods: FG consumption was assessed twice weekly by qualitative list-based 24-h recalls among 1,757 pregnant women (892 control, 865 intervention). The number of days needed to estimate a women's usual prenatal 10-point FG diversity score was calculated using the within-subject coefficient of variation. Regression models, including truncated Fourier series, were fitted to assess seasonal variations in the FG diversity score and the probability of reaching Minimum Dietary Diversity for Women (MDD-W; i.e., ≥5 FGs). Results: The monthly mean FG scores (<5 FGs) and MDD-W prevalence (<45%) were low. Five list-based recalls allowed observed FG diversity to lie within 15% of the true mean in 90% of the estimations (mean ± SD: 40.4 ± 20.7 recalls per woman). Both the FG diversity score and prevalence achieving MDD-W showed responsiveness to seasonal variations with peaks at the end of the dry season (i.e., April/May) and troughs in the rainy season (i.e., August). Conclusions: Five list-based recalls are sufficient to estimate usual FG diversity during gestation; although intra-annual seasonal patterns did modestly affect FG diversity score and MDD-W prevalence. Thus, timing of repeated dietary surveys is critical to ensure non-biased inferences of change and trends in Burkina Faso.